Comparación de tres tratamientos (aerobia, anaerobia y combinado) para la descomposición de materia orgánica en la obtención de biogás y biofertilizante en el Ecuador. - Barragán Torres, Rodolfo Alexander (2024)
In this study, the different types of aerobic, anaerobic and combined decomposition are evaluated to verify their effectiveness in obtaining biogas and biofertilizers from agri-food, livestock, gardening and agricultural waste, and the results show that organic matter from agri-food waste and livestock waste, are particularly suitable for anaerobic digestion, obtaining biogas and biofertilizers with a very high content of macro and micronutrients, including nitrogen, phosphorus, potassium and calcium, which can substantially improve soil fertility, and also have very positive effects on soil fertility. Anaerobic degradation is divided into several phases: hydrolysis, acidogenesis, acidogenesis, acetogenesis, methanogenesis, where organic macromolecules are broken down and transformed into biogas and digestate. On the other hand, the process in aerobiosis, contains glycolysis, Krebs cycle, and concludes with a production of CO2, water, ATP, and also produces biofertilizers with a high content of macro and micronutrients. As for biogas production, the most efficient is anaerobic co-digestion, since it produces 0.00128 m3 of biogas per ton of raw material per day, obtaining 0.008 m3 in a period of fifteen days. The production of biofertilizers the anaerobic co-digestion, although the aerobic one, achieves a better yield, generating values of 0.026 and 0.030 m3 per ton of raw material